Dispositivos de apoyo diseñados para niños con discapacidad neuromotora - Kruzynski, Cecilia Inés (2018)
The University of Engineering- UNJu carried out the design and preparation of support devices for children of APPACE (Cerebral Paralyze Protection Association) with neuromotor disabilities, of school age. The designs were made for certain motor problems detected and characterized in interviews and with information provided by APPACE. The design of a mouse adapter and a portable board, made with the 3D printer; a chair adapter in cardboard and a kalimba (musical instrument) in wood. The digital modeling of the pieces was carried out to then be manufactured based on the different technological requirements.